Fifty years of regional inequality in China: A journey through central planning, reform, and openness - Ravi Kanbur; Xiaobo Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper constructs and analyses a long-run time-series for regional inequality in China from the Communist Revolution to the present. There have been three peaks of inequality in the last fifty years, coinciding with the Great Famine of the late 1950s, the Cultural Revolution of the late 1960s and 1970s, and finally the period of openness and global integration in the late 1990s. Econometric analysis establishes that regional inequality is explained in the different phases by three key policy variables; the ratio of heavy industry to gross output value, the degree of decentralization, and the degree of openness. – inequality ; China ; regional inequality
Keywords: D63; O18; P27; 330; Wirtschaftsgeographie; Regionalstruktur; Räumliche Verteilung; China